Brainstem auditory evoked potentials and middle latency auditory evoked potentials in patients with impaired glucose tolerance - ÇİPRUT, AYŞE AYÇA; TANRIDAĞ, TÜLİN (WILEY, 2008)
Aims The aim was to investigate the effects of impaired glucose tolerance (IGT) on the central nervous system via brainstem auditory evoked potentials (BAEPs) and middle latency auditory evoked potentials (MLAEPs), and on the peripheral nervous system via nerve conduction studies (NCS). Methods Thirty patients with IGT and 20 control subjects underwent NCS, BAEPs and MLAEPs. Results Tibial distal motor latencies were significantly prolonged in the IGT group; no differences in other parameters, including BAEPs and MLAEPs, were observed between the IGT and control subjects. Conclusion Brainstem involvement may not be seen in IGT patients as in DM. The was no obvious electrophysiological finding indicating peripheral nervous system disfunction in our patients.
Keywords: BAEPs; impaired glucose tolerance; MLAEPs; CORTICAL-LESIONS; RESPONSES; NEUROPATHY